PENERAPAN METODE CF (CERTAINTY FACTOR) PADA DIAGNOSA PENYAKIT IKAN NILA - Hidayati, Permata Ika (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
Tilapia is a fish that is susceptible to disease. Pests and diseases that can attack tilapia fish can come from mushrooms or molds, parasites, bacteria and viruses. In District Malang many Nila fish farmers who have difficulty in detecting the disease because of the many diseases that exist. If wrong in detecting the disease then will cause death in large amount. To help overcome these problems, it is designed a system of disease diagnosis experts on tilapia by using the application of expert system of disease diagnosis on tilapia fish with certainty factor method. The purpose of research on the application of Certainty Factor method on Tilapia fish is to know the type of fish disease from the symptoms of fish symptoms of the disease will be calculated by Certainty Factor method so that the accurate type of disease will be obtainedKeyword: Application program on Tilapia, Certainty Factor